2011
DOI: 10.3171/2010.9.jns10151
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative nausea and vomiting in patients after craniotomy: incidence and risk factors

Abstract: The overall incidence of PONV within 24 hours after craniotomy was approximately 50%. One possible reason is that intracranial surgeries pose an additional and independent risk factor for vomiting, especially in female patients. Patients undergoing craniotomy should be identified as high-risk patients for PONV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 28 publications
0
56
2
3
Order By: Relevance
“…21 Although PONV symptoms generally occur and resolve in the early post-operative period, cardiac surgery patients reportedly experience persistent GI symptoms for 4e6 weeks post-surgery. 7 Therefore, PONV has implications not only for immediate perioperative outcomes, but also for post-discharge quality of life, cardiac rehabilitation attendance, and return to work. Finally, side effects associated with anti-emetic medications, such as delirium, 22 as well as complications of PONV may result in extended lengths of stay, which in turn directly affect costs to the health care system.…”
Section: Introductionmentioning
confidence: 99%
“…21 Although PONV symptoms generally occur and resolve in the early post-operative period, cardiac surgery patients reportedly experience persistent GI symptoms for 4e6 weeks post-surgery. 7 Therefore, PONV has implications not only for immediate perioperative outcomes, but also for post-discharge quality of life, cardiac rehabilitation attendance, and return to work. Finally, side effects associated with anti-emetic medications, such as delirium, 22 as well as complications of PONV may result in extended lengths of stay, which in turn directly affect costs to the health care system.…”
Section: Introductionmentioning
confidence: 99%
“…The preoperative median of GCS was 15 (range, 11-15) in patients of elective group and 14 (range, [3][4][5][6][7][8][9][10][11][12][13][14][15] in patients of non-elective group (p<0.001). The median preoperative period was 5 days (range, 1-62 days) in elective surgeries and 2 days (range, 1-12 days) in the non-elective group (p<0.001).…”
Section: Resultsmentioning
confidence: 93%
“…(15) Interestingly, it has been demonstrated that female sex and the absence of steroids intra-operatively are associated with an increased risk of nausea and vomiting. (15) In patients who underwent emergency skull surgery there were more cases of hypotension, arrhythmia, and cardiac arrest, and greater use of vasoactive drugs in comparison with elective surgery patients. One study that followed patients who underwent electives and emergencies neurosurgeries identified only 0.6% of cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of its pharmacodynamic properties, it has an adequate absorption in the gastrointestinal tract and excellent blood–brain barrier penetration. Scopolamine has also been reported to be effective in the prevention of PONV (1, 2, 5, 10, 15, 17, 1922). The literature showed that IV or intramuscular scopolamine has a short half-life in plasma and may lead to dose-dependent side effects such as excessive drowsiness, agitation, hallucinations, dizziness, dry mouth, and lethargy.…”
Section: Introductionmentioning
confidence: 99%